Notes on the type specimens of names in Aconitum (Ranunculaceae) at Central National Herbarium (CAL) - Kumar, Anand; Ghoshal, Partha Pratim; Bharati, Kumar Avinash (Phytotaxa, 2020)
The type specimens belonging to the genus Aconitum available in Central National Herbarium (CAL) are documented with relevant notes. A total of 92 type specimens belonging to 29 taxa are enlisted, it includes 2 holotypes, 2 isotypes, 1 paratype, 12 lectotypes, 25 isolectotypes, 49 syntypes and 1 original material. Lectotype for seven names, A. bakeri, A. ferox subsp. ferox var. crassicaulis, A. ferox subsp. ferox var. flavidiflora, A. ferox subsp. ferox var. laxiflora, A. gammiei, A. insigne and A. wallichianum have been designated here. Second-step lectotype is also designated here for five names, A. deinorrhizum, A. delavayi, A. jucundum, A. soongaricum and A. transsectum.